PENGARUH LATIHAN OREGON SHIFT DRILL TERHADA KELINCAHAN PADA TIM SEPAKBOLA MADRASAH TSANAWIYAH HAYATUL ISLAM KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Juita, Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT Result the indetification problem that football team Mts hayatul Islam districts Pangean Singingi Kuantan district has not had a good physical condition especially agility ( agility ) . This is because lack of exercise leads to physical conditions proficiency level . By because aims to determine whether there are effects of exercise on the Oregon Shift agility drills ( agility ) on students  football team in Mts hayatul Islam  districts Pangean Singingi Kuantan district . Issues raised in this study is " What are the effects of exercise Oregon Shift Agility Drill Against the Islamic  hayatul  Mts  districts Pangean Singingi Kuantan district ? " . Study aimed to determine the effect of the Agility Drill Oregon on Mts hayatul Islam districts Singingi Kuantan district Pangean research hypothesis proposed in this study is that there is the effect of exercise on the Oregon Shift Drill agility on the football team Mts hayatul Islam districts Pangean Singingi Kuantan district .This study is an experimental research . This research was carried out on the football team Mts hayatul Islam districts Pangean Singingi Kuantan district . Data were obtained and collected through the initial test and final test before and after exercise drill Shift Oregon . The data obtained were analyzed descriptively . Results of t test analysis yield was 7.31 t and 1,734 t table at the significant level of 0.05 . Means of t > t table . It can be concluded from the greater Ho Hi . This gives the conclusion that there is a significant effect of exercise on the Oregon Shift Drill Agility at Agility on Mts hayatul Islam districts Pangean Singingi Kuantan district .Keywords : Oregon Shift Drill exercises . agility